Immigrants and the Distribution of Income: National and International Comparisons - Peter Saunders (Luxembourg Income Study (LIS), 1994)
This paper explores the income distribution position of immigrants and nonimmigrants using three different approaches. The results indicate that there is virtually no difference between the distributional profiles of immigrant and nonimmigrant families in Australia. However, when a similar analysis is performed cross-nationally, it is found that immigrants in Australia and Canada perform considerably better, in terms of distributional outcomes, than in either Germany or the United States.
Keywords: 330; Einkommensverteilung; Arbeitsmigranten; Australien; Deutschland; Kanada; USA; Italien